RESEPSI MAHASISWA ILMU KOMUNIKASI UNIVERSITAS ISLAM NEGERI ALAUDDIN MAKASSAR TERHADAP KONTEN YOUTUBE SATU PERSEN-INDONESIAN LIFE SCHOOL (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2024)
This research focuses on the analysis of receptions on the One Percent YouTube Channel regarding assertive communication techniques content. The aim was to find out how UIN Alauddin Makassar Communication Science students interpreted content about assertive communication and how the results of the reception process of UIN Alauddin Makassar Communication Science students towards the content. The result of this reception process is also called decoding. This study uses a qualitative research method with a descriptive approach through Stuart Hall reception analysis data collection techniques. In this case, Stuart Hall classifies the results of audience interpretation or what is called decoding in three positions, namely; hegemony-dominant position, negotiation position, and opposition position. The results of this study show that in the reception process, the audience interprets the content in different ways determined by the understanding and experience of each informant. The results of the interpretation of the One Percent content of Indonesian Life School show that four out of thirteen informants are in hegemony-dominant positions, while the rest are in negotiation positions and there are no informants in opposition positions. This shows that UIN Alauddin Makassar Communication Science students in this case are the informants involved, most of them have known and applied assertive communication techniques, both before watching the One Percent assertive communication techniques content and after watching it. This study implies that it is hoped that the audience can be wiser in their media consumption and that each individual can select media content that suits their preferences. The researcher hopes that there will be further research on assertive communication so that the benefits and values of this research will be more numerous, and hopefully, this research can be one of the learning media and references for further research in researching and studying more deeply, especially related to the study of reception analysis on social communication issues through mass media.